There is business like show business! What marketing scholars and managers can learn from 40~years of entertainment science research - Ronny Behrens; Ann-Kristin Kupfer; Thorsten Hennig-Thurau (Journal of the Academy of Marketing Science, 2024)
For over four decades, scholars have developed the field of entertainment science, establishing a thorough understanding of the business behind filmed, recorded, written, and programmed media products and services, encompassing consumer behavior and strategic decision-making. Building on six foundational characteristics that jointly define entertainment offerings (i.e., their hedonic, narrative, cultural, creative, innovative, and digital nature), we synthesize key findings from entertainment science research. Since each of these characteristics can be found individually in various industries, this review offers substantial potential for learning beyond the entertainment world. Leveraging the entertainment industry's pioneering role in major cross-industry trends, including virtual worlds and generative AI, we then provide best practices for adapting to these developments. We conclude by proposing a comprehensive agenda for future research on each of the foundational entertainment characteristics within the field of entertainment science and beyond.
Keywords: 330; Entertainment; Hedonic consumption; Movies; Video games; Virtual worlds; Generative AI; Research agenda